Case Report: Multidisciplinary discussion and management of a case involving a non-seminomatous germ cell tumor complicated by the presence of cancerous thrombus in the inferior vena cava - Wang, Qian; Zeng, Hong; Zhu, Qiyu; Dai, Jindong; Zhang, Ming; Wan, Sicheng; Shen, Pengfei (Frontiers in Oncology, 2025)
Testicular cancer predominantly manifests in younger males. It demonstrates a favorable response to cisplatin-based chemotherapy and exhibits a promising overall survival. Nevertheless, the emergence of certain rare complications, such as the development of an embolus in the vena cava due to cancer, suggests that the tumor exhibits a high degree of aggressiveness and is associated with a poorer prognosis. We present a case of stage IIIC mixed malignant germinoma with metastases to both lungs, left kidney, right paravascular iliac lymph nodes, periaortic lymph nodes, and an inferior vena cava tumor thrombus. Following Multi-disciplinary Team (MDT) discussion, treatment modalities including surgery and adjuvant chemotherapy were devised, resulting in optimal therapeutic outcomes without complications or significant adverse reactions.